Vector bundles over noncommutative nodal curves - Drozd, Yu. A.; Voloshyn, D. E. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We describe vector bundles over a class of noncommutative curves, namely, over noncommutative nodal curves of string type and of almost string type. We also prove that, in other cases, the classification of vector bundles over a noncommutative curve is a wild problem.